2002
DOI: 10.1161/01.cir.0000030185.67510.c0
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and Serum Angiogenic Activity Is Associated With Low Prevalence of Ischemic Complications in Patients With Giant-Cell Arteritis

Abstract: Background— Vascular inflammatory lesions from patients with giant-cell arteritis show a remarkable amount of neovascularization, but its clinical implications have never been investigated. Methods and Results— To assess the clinical relevance of neovascularization in giant-cell arteritis, angiogenesis was measured in temporal artery sections from 31 patients with biopsy-proven giant-cell arteritis by staining en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 37 publications
3
59
0
Order By: Relevance
“…The same authors described a weaker angiogenic response in GCA patients with ischemic events and in those with low systemic inflammatory response (21). Finally, they found that IL-6 is able to stimulate endothelial cell proliferation and differentiation into capillary-like structures and to exert a full angiogenic activity in ex vivo (aortic ring) and in vivo 296 Salvarani et al…”
Section: Discussionmentioning
confidence: 91%
“…The same authors described a weaker angiogenic response in GCA patients with ischemic events and in those with low systemic inflammatory response (21). Finally, they found that IL-6 is able to stimulate endothelial cell proliferation and differentiation into capillary-like structures and to exert a full angiogenic activity in ex vivo (aortic ring) and in vivo 296 Salvarani et al…”
Section: Discussionmentioning
confidence: 91%
“…This study also found that four PMR patients became disease-free. Several studies, however, have suggested that patients with a lower inflammatory response without an increase in IL-6 expression were at a higher risk of developing ischemic manifestations than were other patients [92], since the angiogenic activity of IL-6 offers protection against ischemia in GCA [93]. These findings indicate that further clinical studies are required to evaluate the efficacy and safety of tocilizumab for GCA and Takayasu arteritis.…”
Section: Gaint Cell Arteritis and Takayasu Arteritismentioning
confidence: 98%
“…[13][14][15] Cells were grown until confluence, passed at a ratio of 1 to 4, and used for experiments after the second to fourth passages. Recombinant IL-6 and recombinant soluble IL-6 receptor (sIL-6R) (both from R&D Systems) were diluted in RPMI 1640 (Invitrogen) with 0.1% bovine serum albumin (Sigma) to make a stock solution of 1 and 10 ng/L, respectively.…”
Section: Endothelial Cell Growth Assaymentioning
confidence: 99%
“…Recombinant IL-6 and recombinant soluble IL-6 receptor (sIL-6R) (both from R&D Systems) were diluted in RPMI 1640 (Invitrogen) with 0.1% bovine serum albumin (Sigma) to make a stock solution of 1 and 10 ng/L, respectively. Confluent HUVECs were released with trypsin-EDTA (Invitrogen) and resuspended in complete growth medium 13 diluted at 50% in plain RPMI 1640. Cells were plated in flat-bottomed 96-well plates at 5000 cells/well, with the addition of recombinant IL-6 and/or recombinant sIL-6R at various concentrations, and incubated at 37°C in 5% CO 2 for 1 to 4 days.…”
Section: Endothelial Cell Growth Assaymentioning
confidence: 99%
See 1 more Smart Citation